Effect of washing, soaking, and cooking methods on perfluorinated compounds in mackerel (Scomber japonicus). Issue 8 (8th July 2020) - Kim, Min‐Joo; Park, Jihyun; Luo, Li; Min, Juhyun; Kim, Jung Hoan; Yang, Hee‐Deuk; Kho, Younglim; Kang, Gil Jin; Chung, Myung‐Sub; Shin, Sangah; Moon, BoKyung
Abstract: Perfluorinated compounds (PFCs) are environmental pollutants, and dietary intake is a major route of human exposure to them. We aimed to see the effects of washing, soaking, and cooking (grilling, braising, frying, and steaming) on the change of PFCs in mackerel fillets and PFCs before and after each treatment were analyzed using LC‐MS/MS. Washing resulted in a decrease in the PFC content of mackerel (average 74%) comparing to control. Among the 19 PFCs detected, perfluorobutanoic acid and perfluorotridecanoic acid (PFTrDA) were found to be abundant after washing. Soaking mackerel in sake reduced its PFC content by 51%, whereas soaking in rice‐washed solution reduced by 80% comparing to control. All the four cooking methods were effective in reducing the PFC content of mackerel. The degree by which the PFC content decreased varied with the cooking method: grilling (91%), steaming (75%), frying (58%), and braising (47%) comparing to uncooked sample. In addition, when mackerel was braised with potato, PFCs decreased more in fillet than the ones without potato. PFCs in potato increased after cooking with mackerel. The excessive consumption through the mackerel was 0.1997 ng/kg bw/day and 0.7987 ng/kg bw/day, respectively. These exposure levels were well below the tolerable daily intake values of both compounds (PFOS, 150 ng/kg bw/day; PFOA, 1, 500 ng/kg bw/day). The results of this study indicated that employing appropriate pretreatment and cooking methods could be an effective way to reduce the dietary exposure to PFCs in mackerel. Abstract : Soaking mackerel in rice‐washed water reduced its perfluorinated compound (PFC) content by 80%. PFCs in mackerel were reduced by cooking, and grilling was the most effect cooking method. It was suggested that employing appropriate pretreatment and cooking methods could be an effective way to reduce the dietary exposure to PFCs in mackerel.